Wyzwania oraz kierunki rozwoju edukacji w zakresie biotechnologii na podstawie doświadczeń w Anglii = Challenges and patterns of development in biotechnology education based on the experience of England - Bryś, Katarzyna; Machnicka, Beata; Kowalski, Mirosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Biotechnology has a growing influence on the economies of nations and on socio-political decisions. Biotechnology education influences the present and future electorate in a meaningful way. England was the first to recognise this fact and was a leader in the development of biotechnology education at the turn of the 20th and 21st century. Political changes and "isconceptions" with GM food significantly influenced the perception of biotechnology and negatively affected biotechnological education. The factors hampering innovation were also an international phenomenon.
Keywords: edukacja biotechnologiczna; kształcenie biotechnologiczne; sugestie edukacyjne; zalecenia edukacyjne; Anglia; biotechnology education; educational suggestions; England